EFEKTIVITAS KINERJA PENYULUHAN TERHADAP PELAKSANAAN PENYULUHAN TENTANG PERATURAN MENTERI-KELAUTAN PERIKANAN NOMOR 56/PERMEN-KP/2016 DI DESA MUARA BADAK ILIR KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Oktilla Aufa; Bambang Indratno Gunawan; Oon Darmansyah (2339-1324, 2019)
This study was conducted for 6 months. It was started from October 2018 until March 2019. The purpose of this study was to find out whether the elucidation has been effective implemented the performance in prohibition of catch the Crab (scyllaseratta) in Muara Badak village. This study also was to find out the problems was faced by the investigator related to the prohibition policy of the crab with certain measure and the female who laid the eggs in the study location. The sampling method in this study was census method. The data was analysed with descriptive quantitative method with the Likert- Scale based on the answer from 24 questions to measure the effectiveness of investigator’s performance toward the implementation of elucidation about PERMEN-KP NOMOR 56/PERMEN-KP/2016 with the total 50 respondents. This study used Quantity of Work, Quality of Work, Job Knowledge, Creativenes, Cooporation, Dependability, Initiative, Personal Qualities as the indicators of investigator’s performance. The findings of the study showed that the effectiveness of investigator’s performance toward the implementation of elucidation about PERMEN-KP NOMOR 56/PERMEN-KP/2016 partially based on the indicators of Quantity of Work with the score 5,34 Job Knoeledgewith the score 6,46, Cooporation with the score 5,12, Initiativewith the score 5,38, Personal Qualitieswith the score 6,5 was in average category. Overall the indicators were in average category with the score 39,86. Thus the performance of extension agents in Muara Badak ilir Village, Muara Badak Subdistrict, Kutai Kartanegara Regency is said to not be good enough in carrying out its duties as a socialization of the PERMEN-KP NOMOR56 / PERMEN-KP2016